Tom Clancy's Op-Center. Dark zone - Rovin, Jeff; Clancy, Tom, 1947-2013; Pieczenik, Steve R; Galdorisi, George, 1948- (Clancy, Tom, 1947-2013. Tom Clancy's Op-center., 2017)
"The brutal murder of an undercover agent reveals a plot to incite a full-fledged war between Russia and Ukraine" -- Back cover.